Exploring Digital Competence: key concepts, evolving terminologies and core competencies - Israilova , Dilkhumor (The Lingua Spectrum, 2025)
In the digital age, the concept of digital competence has gained critical significance, prompting a diverse range of academic and institutional definitions. This article provides a comprehensive review of related terms and conceptual frameworks, including computer literacy, information literacy, media literacy, e-literacy, digital literacy, and e-competence. It traces the historical development of these concepts and highlights their evolution in response to technological advances and societal needs. By examining key definitions and models proposed by UNESCO, the European Commission, and scholars such as Gilster, Eshet-Alkalai, and Ferrari, the review identifies both overlaps and distinctions among the terms. The analysis reveals two primary perspectives: one that treats digital competence as a convergence of multiple literacies, and another that positions it as a distinct and holistic literacy. Ultimately, this synthesis contributes to a clearer understanding of digital competence as a multifaceted and dynamic construct essential for effective functioning in digital environments across educational, professional, and personal contexts.